Enhanced Vasoconstriction Mediated by α1-Adrenergic Mechanisms in Small Femoral Arteries in Newborn Llama and Sheep Gestated at Low and High Altitudes - Moraga, Fernando A.; Reyes, Roberto V.; Ebensperger, Germán; López, Vasthi; Llanos, Aníbal J. (Frontiers in Physiology, 2021)
The authors previously demonstrated that newborn llama (NBLL) express high levels of α1 adrenergic receptors, which provide a potent vasoconstriction response when compared with newborn sheep (NBSH) gestated at sea level. However, data regarding the impact of chronic gestational hypobaric hypoxia on α-adrenergic vasoconstriction in the neonatal life has not been studied. We evaluated if gestation under chronic hypobaric hypoxia modifies α1-adrenergic vasoconstrictor function in NBLL and NBSH. We compared the vasoconstrictor response induced by potassium and α-adrenergic stimuli in isolated small femoral arteries of NBLL and NBSH gestated at high altitude (HA; 3,600 m) or low altitude (LA; 580 m). The maximal contraction (RMAX) and potency (EC50) to potassium, noradrenaline (NA), and phenylephrine (PHE) were larger in HA-NBLL than LA-NBLL. RMAX to potassium, NA, and PHE were lower in HA-NBSH when compared with LA-NBSH and potency results were similar. Competitive blockade with prazosin showed that RNLL LA/HA have a similar pA2. In contrast, NBSH had increased pA2 values in HA when compared with LA. Finally, small femoral arteries denudated or treated with LNAME in LA and HA lacked NO or endothelium participation in response to PHE stimulation. In contrast, NBSH displayed that denudation or blockade with LNAME support NO or endothelium participation in response to PHE activation. In conclusion, HA chronic hypoxia enhances α1 adrenergic receptor activity in small femoral arteries in NBLL to a higher degree than NBSH, implying a higher vasoconstriction function.